Octopus Plushie / Nur Nabila Ismail - Ismail, Nur Nabila (2021)
At the end of the business opportunity, I managed to get a lot of knowledge about businesses in the real world. I also get opportunity to run a business on my own and describe the strength and weakness of the business. From this business opportunity also, I managed to identify the aspects that can be approved over time. The business opportunity I decided to choose is Octopus Plushie. The main course of the product is a sweet and cute plush octopus doll. This Octopus Plushie is a viral and trending doll that were popular among citizens and has been recognized by all people in Malaysia. It can make everyone world such a better place. Reversible flip octopus plush stuffed toy is a soft animal that can use as a home accessories, doll children gifts and also baby companion plush toy. This also can make customer’s life happier. This is due to the insufficient of doll that offers a very cute and attractive of the products. Reversible Octopus Plushie is easy to flip inside out so customers can show their mood to the world. These super soft toys are perfect for playing, collecting & cuddling. A cute reversible plush Octopus with two different expressions. For example, smiley and sadness or angry expressions. There are variable type of sizes and colours that customers can choose for this plushie. They can give this plushie to everyone they want such as family, friends and their lovers. Exceeding customers’ expectations is achieved through passionate hard work and a dedication to reaching new standards. Because of the large number of citizens in Malaysia,everybody can have it and it also suitable for every standard of age. For example, it suitable for kids, teenagers, students, middle ages people and also for adults. It also very affordable price that everyone can buy and enjoy it. Next, my vision is to become a leading desserts among all the other brands or products.